APPLICATION UTILISATION OF API AND B-SHARE APPLICATION FOR PROVIDING BLOOD AVAILABILITY INFORMATION - Fadhila Putri, Mutia; Dwi Oktariana, Siti (Yayasan Nuraini Ibrahim Mandiri, 2023)
lack of information about the availability of blood to be a problem that is not uncommon in the daily life, there are many medical cases that require blood transfusion procedure. Practically, the hospital will entrust the patient’s family to find blood bags with the required blood type. Families with little knowledge about where to find blood will encounter confusing situations. Whereas they have to find it fast. if a blood transfusion is done too late, then even death may occur, because of this, it is expected that the existence of a public service that can provide information quickly and accurately blood that can be utilized by the community. In the development of the technology of internet this day it could be used to increase the public service and fulfill the needed of information, especially for the government who hasn’t provided the information about blood availability location based on geolocation that should be easily accessed by all people. Because information about the availability of blood is very important information to be known to the community as of the Information needed so we would develop the geographical information system to search the location of PMI and hospitals having the blood supply. The chosen method for this program is Requirement Analysis, Conceptual Modeling, Implementation, and testing. This method is the one of development method of software engineering so that produced an application that could solve the problem by providing a software that integrates blood stock information across PMI and hospitals branches in all over Indonesia. This information system integrates blood stock information across PMI branchesandhospitals all over Indonesia, providing access to real time blood stock updates to people, providing information about PMI branchesandhospitals locations across Indonesia in the shape of a map complete with the contact number